Prediking in die wêreld van die hoorders - Pieterse, HJC (Acta Theologica, 1995)
The problem which this article addresses is the need of the congregation to hear the living Word of God and the implications of this word in their concrete world of a society in transition. The author argues that the preacher should reckon with three worlds in the process of understanding the text for the sermon, instead of the usual assumptino that hermeneutics has to do with two worlds: the text and the contemporary situation. The world of listeners has become diffuse, complicated and is marked by plurality. The problem is discussed from a hermeneutical-communicative perspective, and insights are developed which could help the preacher to navigate the message of the text into the concrete world of the congregation.